Assessment Of The Performance Of Common 2-D Resistivity Arrays - ., Amsir (2018)
The assessment of the performance for electrical resistivity arrays were carried out by comparing the penetration depth, horizontal / vertical coverage and sensitivity index of each array. The research objective is to identify the performance of common arrays; Wenner (WNR), Wenner-Schlumberger (WSCH), Dipole-dipole (DPD), and Pole-dipole (PDP) relative to each other (PDP:WNR, PDP:WSCH, PDP:DPD, DPD:WNR, DPD:WSCH and WNR:WSCH) and presented in numerical form. Five synthetic models and one field study were created for assessment of the performance using the four different arrays.